ANALISIS MEKANISME PENGGUNAAN AKAD RAHN DALAM TRANSAKSI GADAI SAWAH MENURUT PERSPEKTIF HUKUM ISLAM DI DESA POLENGA KECAMATAN WATUBANGGA KABUPATEN KOLAKA - Lilis Antiani; M. Zakariah; Kasmiah Kasmiah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The practice of pawning rice fields in the people of Polenga Village, Watubangga District, Kolaka Regency. The mechanism shows that there are several things that are considered burdensome and can harm one of the parties who have contracted. Therefore, the author will examine the practice of pawning that occurs in the people of Polenga Village, Watubangga District, Kolaka Regency, by analyzing problems regarding the perspective of Islamic law on the mechanism of pawning practice, as well as the use of rice fields which are used as collateral for pawning.The main problem in this research is how the mechanism of implementing land pawning (rice fields) in the community of Polenga Village, Kec. Watubangga ?, and what is the perspective of Islamic law on the implementation of pawning land (rice fields) in the people of Polenga Village, Watubangga District ?. The purpose of this study is to determine the implementation mechanism of the pawn practice and the perspective of Islamic law on the pawning mechanism.The research method used includes the type of research in the form of qualitative research, and the data sources of this study are the pawker (rahin) and the pawning recipient (murtahin). Furthermore, the data collection methods used were observation, interviews, documentation and literature study, then the processing and analysis techniques used were descriptive qualitative.The results showed that the pawning system in Polenga Village generally pawned (rahin) came to the pawnshop recipient (murtahin) to borrow money to meet their needs with rice fields as collateral. The right to control or use the rice fields is in the hands of the pawning recipient until the debt is paid off. The right to cultivate is still in the hands of the pawner, but the results are divided in 2 between rahin and murtahin. Debt payment has a time limit for 2 harvests, but if it is due but the pledge is not able to pay the money, the tempo has not been determined anymore so that it can cause the pawning contract to drag on. If viewed from the point of view of implementation the contract has met the pillars and conditions of the pawn The practice of pawning which is carried out indefinitely with the use of rice fields as collateral is fully controlled by the pawn recipient is not valid according to Islamic law.